A multicultural study of biometric privacy concerns in a fire ground accountability crisis response system. Issue 5 (October 2016) - Carpenter, Darrell; Maasberg, Michele; Hicks, Chelsea; Chen, Xiaogang
Highlights: Anglo and Hispanic ethnic groups perceive biometric privacy issues differently. Use of biometric systems may alleviate some, but not all, types of privacy concerns. Anglo and Hispanic ethnic groups reacted differently after exposure to system. Biometric data vulnerability concerns of Anglos were lower than Hispanics after use. Hispanics had higher accountability concerns related to biometrics prior to use. Abstract: Biometric technology is rapidly gaining popularity as an access control mechanism in the workplace. In some instances, systems relying on biometric technology for access control have not been well received by employees. One potential reason for resistance may be perceived privacy issues associated with organizational collection and use of biometric data. This research draws on previous organizational information handling and procedural fairness literature to frame and examine these underlying privacy issues. Perceived accountability, perceived vulnerability, and distrust were distilled from the previous literature as the primary dimensions of employee privacy concerns related to biometric technology. This study assesses the effects of these privacy concerns, how they vary based on the cultural influences of Anglos and Hispanics. Fire ground accountability is a critical management objective in the firefighting domain. In multi-unit or multi-agency crisis response scenarios, the on-scene incident commander tracks and accounts for each first responder. This research designed and deployed a new fire ground accountability system that tracked firefighters through finger pattern-based biometric logins to their assigned positions on the firefighting apparatus. An instrument measuring level of privacy concern on three underlying dimensions and demographic data was developed, validated and administered in a quasi-experimental field study. A pre-test–post-test survey methodology was employed to detect potential differences in privacy concerns as familiarity with the system increased. The study shows that Anglo and Hispanic subjects frame privacy issues differently associated with use of biometric technology in a fire ground accountability system. Finally, the study showed that some privacy concerns such as distrust and perceived vulnerability can be alleviated through system use with changes in post-use privacy concerns moderated by ethnic affiliation.